Conodonts from the Davidsville Group, northeastern Newfoundland - Stouge, Svend (Canadian Journal of Earth Sciences, 1980)
Conodonts from the basal part of the Davidsville Group, Botwood Zone of Newfoundland, are assigned a late Llanvirn to early Llandeilo age. Other fossil groups suggest a time range of Llanvirn to early Caradoc, and the conodonts are in accordance with the previous datings. The conodont fauna is contemporaneous with that of Cobbs Arm Limestone, central Newfoundland, and no major difference between the two faunas exists.